HUBUNGAN GREEN MARKETING DAN KINERJA BISNIS: TINJAUAN LITERATUR SISTEMATIK - Syamsul Hidayat, Mohamad; Kasnowo, Kasnowo; Dwihandoko, Toto Heru (Gapenas Publisher, 2024)
The company's environment is dynamic and can have an impact on company performance. One of them is government regulations related to environmental sustainability. Companies must be aware of this in order to make products or services that are environmentally friendly and safe for consumers. Many companies carry out green promotions in order to introduce products which are environmentally friendly both in terms of packaging and materials used in production. There are several studies and discussions that still have different results regarding the relationship between green marketing and companies and green marketing variables. Therefore, the aim of this article is to provide a clear understanding clearer about the relationship between green marketing and business performance by conducting a systematic literature review of 283 Scopus indexed articles published by Elsevier, Springer, Emerald and SAGE. From the 283 articles, we selected a minimum of 40 quotes. Then we further selected 10 published articles that were relevant from 2012 to 2024. The results of the analysis identified that in general green marketing has a relationship and influence on companies